Relationship between Knowledge and Attitudes with Contraceptive Use among Women of Childbearing Age at the Comoro Health Centre, Dili, Timor Leste - Marilia Juvi Gonçalves; Ni Luh Putu Suariyani; Nyoman Tigeh Suryadhi (Universitas Udayana, 2014)
Background and purpose: Timor-Leste's population growth rate increased by 2.4%. Data in 2013 showed the contraceptive use among women of childbearing is only 37.3%. This study aims to determine the relationship between knowledge and attitudes with contraceptive use. Methods: A cross-sectional was conducted with 83 female respondents. The dependent variable was contraceptive use. Knowledge concerning contraceptive use and attitudes were the independent variables. Data were collected through a self-administered questionnaire, however, for illiterate respondents, researcher assisted with questionnaire completion. Data analysis was conducted in stages: univariate and bivariate (chi-squared test). Results: The majority of respondents 41 (49.4%) aged 25-34 years, 37 (44.6%) respondents obtained high school education, 62 (74.7%) were housewives, good knowledge regarding family planning (39.8%) had positive attitude (45,8%). Results indicate that there was a significant relationship between maternal knowledge (p=0.006) and attitude (p=0.017) with contraceptives use among women of childbearing age. Conclusion: Level of knowledge and attitude are correlated to contraceptive use among women at Comoro Health Centre, Dili District, Timor Leste.